Sistem Diagnosis Penyakit Kucing Menggunakan Metode Naive Bayes - Ahmad Fuyudi Wijaya; Nurul Hidayat; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
One of the most popular pets in Indonesia is the cat. According to experts Didik Saptono cat who has name felin silvertis cotus is a kind of carnivore. Many cat keepers 1 find it difficult to take care of their beloved cat when sick and one way to find out the cat'sdiseases seen from the symptoms that arise in cats and consultation of veterinarians, However there are some that prevent the keeper to go visitthe veterinarian ie limited time, distance and cost. An alternative solution overcome this problem by creating a system that can help cat keepers in diagnosing cat diseases.The method thatcan be used in this Expert System is Naive Bayes. The method is implemented on the inference engine Expert System in order to make a conclusion based on existing knowledge on the knowledge base. Results obtained after a system accuracy test of 85% indicating that the Naive Bayes method is suitable for cat disease cases.